"Twin language": a risk factor for language impairment? - Bishop, D; Bishop, S (1998)
Retrospective parental report of earlier "twin language" was obtained for two groups of twins. Sample G consisted of 94 twin pairs between the ages of 7 and 13 years recruited through the school system as a general population sample. Sample L consisted of 82 twin pairs between the ages of 7 and 13 years who had been recruited for a genetic study; of these twin pairs at least one of the twins had a speech-language impairment persisting to school age. Parental report of twin language was higher (around 50%) for children with speech-language impairment than for those with normal language (11%). Consistent with this, children with twin language obtained significantly lower mean language scores than other children, although their mean nonverbal IQ was equivalent. The exceptions were a handful of children whose parents described use of a "private language" that coexisted alongside normal use of English. These findings are consistent with the view that what is described as twin language is usually use of immature or deviant language by two children at the same developmental level.